Safety and immunogenicity of 3 formulations of a Sabin inactivated poliovirus vaccine produced on the PER.C6® cell line: A phase 2, double-blind, randomized, controlled study in infants vaccinated at 6, 10 and 14 weeks of age. Issue 5 (30th November 2022) - Ong-Lim, Anna Lisa; Shukarev, Georgi; Trinidad-Aseron, Mitzi; Caparas-Yu, Delia; Greijer, Astrid; Duchene, Michel; Scheper, Gert; van Paassen, Vitalija; Le Gars, Mathieu; Cahill, Conor P.; Schuitemaker, Hanneke; Douoguih, Macaya; et al.
ABSTRACT: An inactivated poliovirus vaccine candidate using Sabin strains (sIPV) grown on the PER.C6® cell line was assessed in infants after demonstrated immunogenicity and safety in adults. The study recruited 300 infants who were randomized (1:1:1:1) to receive one of 3 dose levels of sIPV or a conventional IPV based on Salk strains (cIPV). Poliovirus-neutralizing antibodies were measured before the first dose and 28 days after the third dose. Reactogenicity was assessed for 7 days and unsolicited adverse events (AEs) for 28 days after each vaccination. Serious AEs (SAEs) were recorded throughout the study. Solicited AEs were mostly mild to moderate. None of the SAEs reported in the study were judged vaccine related, including one fatal SAE due to aspiration of vomitus that occurred 26 days after the third dose of low-dose sIPV. After 3 sIPV vaccinations and across all dose levels, seroconversion (SC) rates were at least 92% against Sabin poliovirus types and at least 80% against Salk types, with a dose-response in neutralizing antibody geometric mean titers (GMTs) observed across the 3 sIPV groups. Compared to cIPV, the 3 sIPV groups displayed similar or higher SC rates and GMTs against the 3 Sabin types but showed a lower response against Salk types 1 and 2; this was most visible for Salk type 1. While the PER.C6® cell line-based sIPV showed an acceptable safety profile and immunogenicity in infants, lower seroprotection against type 1 warrants optimization of dose level and additional clinical evaluation.